2015
DOI: 10.1097/inf.0000000000000801
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Virologically Suppressed HIV-Positive Children on Antiretroviral Therapy

Abstract: Background Combination antiretroviral therapy (ART) suppresses viral replication in HIV-infected children. The growth of virologically suppressed children on ART has not been well documented. We aimed to develop dynamic reference curves for weight-for-age z scores (WAZ) and height-for-age z scores (HAZ). Methods Children aged <11 years at ART initiation with continuously undetectable viral loads (<400 copies/ml) treated at seven South African ART programs with routine viral load monitoring were included. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…The majority of our participants were virologically suppressed at study exit. Contrary to our findings, a study done in Southern Africa by Keiser et al [29] concluded that baseline high VL was associated with poor growth, but with a small effect estimate. Good adherence to ART is usually associated with successful viral suppression and hence, disease control and a reduction in opportunistic infections, with improved childhood growth.…”
Section: Plos Onecontrasting
confidence: 99%
“…The majority of our participants were virologically suppressed at study exit. Contrary to our findings, a study done in Southern Africa by Keiser et al [29] concluded that baseline high VL was associated with poor growth, but with a small effect estimate. Good adherence to ART is usually associated with successful viral suppression and hence, disease control and a reduction in opportunistic infections, with improved childhood growth.…”
Section: Plos Onecontrasting
confidence: 99%
“…Findings regarding association of immunological status (CD4 count, WHO stage) with growth recovery have been inconsistent, often showing no association after accounting for baseline growth measures [12,16,20,22,25]. In addition, catch up growth often appears to stagnate after 1–2 years on ART even among children with virologic suppression [10,26].…”
Section: Predictors Of Growth Reconstition After Art Initiationmentioning
confidence: 99%
“…Other low-cost screening instruments such as mid-upper arm circumference may be useful for identifying those at greatest risk of growth failure [43]. Development of screening tools for assessing growth rates on ART relative to reference standards may also improve identification of growth failures [26].…”
Section: Challengesmentioning
confidence: 99%
“…[9][10][11] Delayed ART initiation is additionally associated with suboptimal immune reconstitution, bone development, and attainment of growth potential. [12][13][14][15] A study in Zimbabwe that followed up 197 children with a median age of 11 years over 2 years found that ART initiation earlier in life could prevent an annual deterioration of 0.06 in the forced expiratory volume in 1 second (FEV 1 ) z score. 16 In addition, a higher body mass index (BMI)-for-age z score at the time of initiating follow-up was associated with an increase in 0.31 FEV 1 z score per year.…”
Section: Introductionmentioning
confidence: 99%